Politik Hukum, Demokrasi Digital, dan Kekuasaan Partai Politik Menyongsong Pemilu 2024 di Indonesia - Noak, Piers Andreas (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023), 2023)
Legal Politic and Political Party authority in the next 2024 election constellation is a form of democraticacy phase. In this phase political party organization has to deal with various assertions bases on reformation value system. This article observes the effect of digitalization era existence of democracy towards political party as a strength actualization of politic superstructure in the some sides take elaboration of legal politic. This method applied is a normative legal research and the authority determined as a statute approach framework. The author take an explanative analysis on the various literatures. Normatively. There are a strategy transformation of  campaign both of traditional and conventional towards digital technology utilization. Digital media domination is not only applied into politic contestation moment but also to be an information of ideology strengthening as well as political movement by political party. It needs to adapt to digital era especially in the moment when they have to be concentrate in contribution in order political communication become an important thing as a of implementation strengthening digital democraticacy. Politik hukum dan kekuasaan partai politik pada konstelasi pemilu tahun 2024 mendatang adalah bentuk fase demokratisasi. Pada fase ini organisasi partai politik harus menghadapi beragam tuntutan perubahan sesuai tata nilai reformasi. Artikel ini melihat dampak kehadiran era digitalisasi demokrasi terhadap partai politik sebagai aktualisasi kekuatan suprastruktur politik yang pada beberapa sisi mengelaborasi politik hukum. Metode yang digunakan adalah penelitian hukum normatif dan kekuasaan dipandang dalam bingkai statute approach. Penulis melakukan analisis eksplanatif secara kualitatif terhadap beberapa literature. Secara normatif, terjadi perubahan strategi berkampanye secara tradisional konvensional menuju pemanfaatan teknologi digital. Penguasaan media digital bukan hanya digunakan dalam momentum kontestasi politik, tetapi menjadi informasi penguatan ideologi dan gerakan politik oleh partai politik. Partai politik perlu beradaptasi di era digital terlebih saat mereka harus berkontestasi sehingga komunikasi politik menjadi penting sebagai penguatan  penyelenggaraan demokratisasi digital.